2005
DOI: 10.1097/01.pai.0000133058.00588.15
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CDX2, Cytokeratins 7 and 20 in Sinonasal Intestinal-Type Adenocarcinoma

Abstract: CDX2 is a transcription factor expressed by intestinal epithelium. It is considered as a sensitive marker for a colorectal or-less frequently-gastric origin of adenocarcinomas. The pattern of coordinated expression of cytokeratin (CK) 7 and CK20 is also useful for the diagnosis of the origin of metastatic adenocarcinomas. Expression of CDX2, CK7 and CK20 was investigated in 14 cases of sinonasal intestinal-type adenocarcinoma (SIA), a particular tumor with an enteric-cell-type appearance. Formalin-fixed, paraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…We confirmed that CDX-2 and cytokeratin 20 are highly sensitive for sinonasal ITAC, as has been previously shown Intestinal-type adenocarcinoma 6/6 (100) 6/6 (100) [15][16][17][18][19][20]. It is worth noting that the immunostaining was not always diffuse in ITACs: focal positivity for CDX-2 and cytokeratin 20 was seen in 1 of 6 and 2 of 6 cases, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We confirmed that CDX-2 and cytokeratin 20 are highly sensitive for sinonasal ITAC, as has been previously shown Intestinal-type adenocarcinoma 6/6 (100) 6/6 (100) [15][16][17][18][19][20]. It is worth noting that the immunostaining was not always diffuse in ITACs: focal positivity for CDX-2 and cytokeratin 20 was seen in 1 of 6 and 2 of 6 cases, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the two immunostains were complementary; in the 3 cases where one was only focally positive, the other was diffuse. Both markers were consistently negative in non-intestinal surface-type adenocarcinomas, as others have previously demonstrated [15][16][17][18][19][20].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Regarding papillary variants of the intestinal type of adenocarcinoma, these tumors show more nuclear atypia than our tumor and commonly display mucinous differentiation. Immunohistochemically, ITACs are positive for CK20 and express cdx-2 [39] (negative in our case). Sinonasal low-grade tubulo-papillary adenocarcinoma (''terminal tubulus adenocarcinoma'' according to Kleinsasser) is a rare neoplasm characterized by Skalova et al [40].…”
Section: Discussionmentioning
confidence: 76%
“…19,[45][46][47][48][49][50] On the basis of this ubiquity, negative CDX2 expression in adenocarcinoma cannot systematically rule out a diagnosis of colorectal cancer. Especially, the immunohistochemical analysis of a mucinous adenocarcinoma with negative CK20 expression in addition to negative CDX2 expression, located on the right side of the colon of a female patient must be underlined as a potential pitfall of misdiagnosis, where a metastasis could be diagnosed without consideration of a possible microsatellite instability high colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%